Revitalizing the cultural heritage sites of the medieval town of Tansen for the sustainable tourism development - Rana, Paras SJB (Nepalese Culture, 2019)
Tansen is renowned for its natural settings, historic buildings and a living cultural heritage that have remained, from medieval period until now. By UNWTO statistics,internationally, cultural tourism comprises 39% of the total tourism arrivals. This reaffirms that offering greater access to the cultural and heritage assets would give Tansen a competitive edge over the other tourist destinations and increase its attractiveness as a top tourist destination in Nepal. This article is related to study of how the heritage sites could be revived to make the cultural heritage tourism sustainable and regain Tansen’s economic vibrancy that has been depleting in the recent times. The purpose of the study is to examine the current state of the cultural heritage management in Tansen, to examine the prospect of revitalizing the cultural heritage assets and; to examine the role of the local communities in these aspects. The methods used in the study were site observations, a key informant interview of experts including the city Mayor, tourism entrepreneurs, site mangers and opinion survey of tourists and the local community resident. The study shows that local population has a positive opinion and initial enthusiasm on the emerging tourist arrivals after the restoration of Rani Mahal, but their role is marginalized in the process. This is the key proposition to start an initiative for the local communities to actively participate in tourism development projects. ‘Revitalizing the Rani Mahal heritage’ launched through the Public Private Partnership with support from UNESCO could build the trust amongst the high end international as well as domestic tourist and attract more investments to conserve, protect and promote the heritage capital stocks for the Tansen tourism development.